Effect of a 16-day altitude training camp on 3,000-m steeplechase running energetics and biomechanics: A case study - Slawinski, J.; Chiron, F.; Millot, B.; Taouji, A.; Brocherie, F. (Frontiers in Sports and Active Living, 2019)
The purpose of this study was to investigate the effect of a 16-day training camp at moderate altitude on running energetics and biomechanics in an elite female 3,000-m steeplechase athlete (personal best: 9 min 36.15 s). The 16-day intervention included living and training at 1,600 m altitude. A maximal incremental test was performed at sea level to determine the maximal oxygen uptake (V·O2max ). Before (pre-) and after (post-) intervention, the participant performed a specific training session consisting of 10 × 400 m with 5 hurdles with oxygen uptake (V·O2), blood lactate, stride length and stride rate being measured. A video analysis determined take-off distance and landing around the hurdle (DTH and DLH), take-off velocity and landing around the hurdle (VTH and VLH), and the maximal height over the hurdle (MH). The results demonstrated that the mean V·O2 maintained during the ten 400 m trials represented 84-86% of V·O2max and did not change from pre- to post-intervention (p = 0.22). Mean blood lactate measured on the 6 last 400-m efforts increased significantly (12.0 ± 2.2 vs. 17.0 ± 1.6 mmol.l-1; p < 0.05). On the other hand, post-intervention maximal lactate decreased from 20.1 to 16.0 mmol.l-1. Biomechanical analysis revealed that running velocity increased from 5.12 ± 0.16 to 5.49 ± 0.19 m.s-1 (p < 0.001), concomitantly with stride length (1.63 ± 0.05 vs. 1.73 ± 0.06 m; p < 0.001). However, stride rate did not change (3.15 ± 0.03 vs. 3.16 ± 0.02 Hz; p = 0.14). While DTH was not significantly different from pre- to post- (1.34 ± 0.08 vs. 1.40 ± 0.07 m; p = 0.09), DLH was significantly longer (1.17 ± 0.07 vs. 1.36 ± 0.05 m; p < 0.01). VTH and VLH significantly improved after intervention (5.00 ± 0.14 vs. 5.33 ± 0.16 m.s-1 and 5.18 ± 0.13 vs. 5.51 ± 0.22 m.s-1, respectively; both p < 0.01). Finally, MH increased from pre- to post- (52.5 ± 3.8 vs. 54.9 ± 2.1 cm; p < 0.05). A 16-day moderate altitude training camp allowed an elite female 3,000-m steeplechase athlete to improve running velocity through a greater glycolytic—but not aerobic—metabolism.